PENGEMBANGAN BAHAN AJAR BERBASIS TUNJUK AJAR MELAYU DI SEKOLAH DASAR - Aini, Nurul; Eddy Noviana; Otang Kurniaman (Unversitas Katolik Santo Thomas, 2022)
This study aims to develop teaching materials based on Malay teaching and learning in elementary schools for fourth-grade elementary school students. The type of writing is Research and development using a 4D development model. The results obtained that teaching materials based on Malay teaching and learning are very valid and very practical so that they are